1999
DOI: 10.1080/10408419991299257
|View full text |Cite
|
Sign up to set email alerts
|

From Field Barley to Malt: Detection and Specification of Microbial Activity for Quality Aspects

Abstract: Barley grain carries a numerous, variable, and complex microbial population that mainly consists of bacteria, yeasts, and filamentous fungi and that can partly be detected and quantified using plating methods and microscopic and molecular techniques. The extent and the activity of this microflora are determined by the altering state of the grain and the environmental conditions in the malt production chain. Three ecological systems can be distinguished: the growing cereal in the field, the dry barley grain und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
120
1
4

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 58 publications
(172 reference statements)
4
120
1
4
Order By: Relevance
“…Rapid bacterial and fungal growth on the barley occurs during steeping. A study by Noots et al 135 showed intensive growth of Fusarium spp. during the steeping process, even when the original barley had a low level of Fusarium spp.…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…Rapid bacterial and fungal growth on the barley occurs during steeping. A study by Noots et al 135 showed intensive growth of Fusarium spp. during the steeping process, even when the original barley had a low level of Fusarium spp.…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…Conditions that enable grain germination also favour microbial growth. Imbibed water rapidly activates the dormant microbes present in barley and therefore steeping can be regarded as a crucial step in malting with respect to microbial activity 32,41,45 . Microbial activity remains high during germination.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to germinating barley, the malting process involves another metabolically active component: the diverse microbial community that naturally colonizes the grains. The indigenous community harbours a wide range of microbes including numerous species of Gram-negative and -positive bacteria, yeasts and filamentous fungi 17,20,32,41,46 . In addition, each process step can be a source of additional microbes and their metabolites 32,45 .…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of bacteriocins 3,10,22 and antifungal compounds 28 and depletion of nutrients can also play a role 20 . Of significance with respect to sorghum malting is that many anti-microbialproducing lactic acid bacteria have been isolated from samples of raw sorghum 12 .…”
Section: Introductionmentioning
confidence: 99%